(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Among several types of famous sequences that exist in all branches of mathematics, Padovan sequence is one of such sequences possessing amusing properties. In this paper, we shall discuss about Padovan Sequence and determine a special number called Plastic number. We also derive the ratio of its (n+1)st term to the nth term as n is very large, which is called “Limiting Ratio”. Finally we discuss the geometrical interpretation of the terms of Padovan sequence.